Node activity scheduling schemes in large-scale wireless sensor networks - Tian, Di (University of Ottawa (Canada), 2005)
In wireless sensor networks that consist of a large number of low-power, short-lived, unreliable sensors, one of the main design challenges is to obtain long system lifetime without sacrificing sensing quality; i.e. sensing coverage in this context. In this thesis, we first propose a node-scheduling scheme, which can reduce system overall energy consumption, therefore increasing system lifetime, by identifying redundant nodes with respect to sensing coverage and then assigning them an off duty operation mode which has lower energy consumption than the normal on-duty mode. Our scheme aims at completely preserving original sensing coverage. Practically, sensing coverage degradation caused by location error, packet loss and node failure is very limited, not more than 1%, as shown by our experimental results. We implement the proposed scheme in NS-2, as an extension of the LEACH protocol and compare its energy consumption with the original LEACH. Simulation results exhibit noticeably longer system lifetime with our scheme as compared to earlier algorithm. The first scheme we propose aims at completely preserving sensing coverage. This, however, requires each node to get, in some way, the knowledge of its own and its neighbors' location information. Also, in that scheme, each node has to perform some calculations to determine whether to take an off-duty status. To alleviate these restrictions, we propose and study several alternative node-scheduling schemes, which cannot guarantee the complete preservation of the original system coverage, but are nonetheless more light-weighted and flexible than the previous one. The simulation results compare these schemes with the previous one and demonstrate their effectiveness. In a single wireless sensor network, sensors are performing two operations: sensing and communication. Therefore, there might exist two kinds of redundancy in the network. Most of the previous work addressed only one kind of redundancy: sensing or communication alone. Although there have been research efforts trying to combine consideration of coverage and connectivity maintenance in a single activity scheduling, their theoretical basis for safe scheduling integration condition is only applicable in those networks that are initially fully covered by sensors. Random node deployment often makes initial sensing holes inside the deployed area inevitable, even in an extremely high-density network. Therefore, in this thesis, we enhance these works to support general wireless sensor networks by proving another conclusion: "the communication range is twice the sensing range" is the sufficient condition and the tight lower bound to ensure that complete coverage preservation implies connectivity among active nodes, if the original network topology (consisting of all the deployed nodes) is connected. Also, we extend the results to k-degree network connectivity and k-degree coverage preservation.
Keywords: Computer Science.